2009
DOI: 10.2118/111288-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Equalizer Production System and Smart-Well Applications in Full-Field Studies

Abstract: Equalizer production systems and inflow control devices are used to mitigate water or gas-coning problems for mature fields. We have developed new modeling methods to simulate equalizer and interval control valve (ICV) performance in fullfield multimillion-cell reservoir models under a parallel computational environment.The authors present single-well performance predictions with and without an equalizer, and the results are significantly different in some cases. Full-field modeling with equalizers and ICV con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Alhuthali et al (2007) reported optimal waterflood management using rate control by ICD. Su and Dogru (2009) performed modeling of an equalizer production system and smart-well applications in full-field studies. Fernandes et al (2009) discussed the roles of ICDs in optimizing horizontalwell performance.…”
Section: Introductionmentioning
confidence: 99%
“…Alhuthali et al (2007) reported optimal waterflood management using rate control by ICD. Su and Dogru (2009) performed modeling of an equalizer production system and smart-well applications in full-field studies. Fernandes et al (2009) discussed the roles of ICDs in optimizing horizontalwell performance.…”
Section: Introductionmentioning
confidence: 99%